Plasma Concentration of Tumor Necrosis Factor-Stimulated Gene-6 as a Novel Diagnostic and 3-Month Prognostic Indicator in Non-Cardioembolic Acute Ischemic Stroke - Qu, Yewei; Yang, Fan; Meng, Fanwei; Chen, Xi; Zhang, Qingqing; Yu, Tian; Wen, Shirong; Pan, Yujun (Frontiers in Immunology, 2022)
Background Tumor necrosis factor-stimulated gene-6 (TSG-6) is a multifunctional, anti-inflammatory, and protective protein, while the association between TSG-6 and acute ischemic stroke (AIS) remains unclear in humans. This study aims to investigate the potential diagnostic and short-term prognosis predictive values of TSG-6 in non-cardioembolic AIS. Methods A total of 134 non-cardioembolic AIS patients within 24 h after AIS onset and 40 control subjects were recruited. Using an AIS dataset from the Gene Expression Omnibus database and setting the median expression level of TNFAIP6 as the cutoff point, data were divided into TNFAIP6-high and TNFAIP6-low expression groups. Differently expressed genes (DEGs) were extracted to perform gene enrichment analysis and protein–protein interaction (PPI) network. Baseline data were analyzed in a four-group comparison plotted as plasma TSG-6 concentration median and 25th/75th percentiles. The correlative factors of 3-month outcome were evaluated by logistic regression. TSG-6 concentrations and TSG-6-to-interleukin-8 ratios were compared in a block design. A receiver-operating characteristic curve was used to analyze the detective value of TSG-6 and 3-month prognosis predictive values of TSG-6 and TSG-6-to-interleukin-8 ratio. Results Non-cardioembolic AIS patients had significantly higher plasma TSG-6 levels than control subjects (P < 0.0001). The large-artery atherosclerosis group had significantly higher TSG-6 levels than the small-artery occlusion group (P = 0.0184). Seven hundred and eighty-two DEGs might be both AIS-related and TNFAIP6-correlated genes, and 17 targets were deemed AIS-related being closely relevant to TNFAIP6. Interleukin-8 was selected for further study. The National Institutes of Health Stroke Scale and the Acute Stroke Registry and Analysis of Lausanne scores at admission, lesion volume, neutrophil count, neutrophil-to-lymphocyte ratio, and interleukin-8 level were positively correlated with TSG-6 level, respectively (P < 0.0001). The unfavorable outcome group had meaningfully higher TSG-6 levels (P < 0.0001) and lower TSG-6-to-interleukin-8 ratios (P < 0.0001) than the favorable outcome group. After adjusting for confounding variables, elevated TSG-6 levels remained independently associated with 3-month poor prognosis of non-cardioembolic AIS (P = 0.017). In non-cardioembolic AIS, the cutoff values of TSG-6 concentration for detection and 3-month prognosis prediction and the TSG-6-to-interleukin-8 ratio for the 3-month prognosis prediction were 8.13 ng/ml [AUC, 0.774 (0.686–0.861); P < 0.0001], 10.21 ng/ml [AUC, 0.795 (0.702–0.887); P < 0.0001], and 1.505 [AUC, 0.873 (0.795–0.951); P < 0.0001]. Conclusions Plasma TSG-6 concentration was a novel indicator for non-cardioembolic AIS diagnosis and 3-month prognosis. Elevated TSG-6-to-interleukin-8 ratio might suggest a 3-month favorable outcome.